Educating through sport social transformation: Paths for the implementation of handball in public schools in the metropolitan region I of the State of Rio de Janeiro - Dutra , Joel Teixeira; Trotta, Leonardo Monteiro (Seven Editora, 2024)
This book was produced from the experience with discipline of Physical Education, result of the research of the professional master’s degree New Digital Technologies in Education - MPNTD, of the Centro Universitário Carioca, through the dissertation "Educating through sport is social transformation: Handball in public schools of the state education network in the metropolitan regional I of the state of Rio de Janeiro". The discussions about the practice of handball with children and adolescents combined with the research made us realize the need to produce a text that dealt with the stimuli of the sport in the historical and inspiring perspective, being used as an instrument for the implementation of the project. The research investigated the importance of sports activities in the public school Colégio Estadual Antônio da Silva, located in the city of the state of Rio de Janeiro of the Metropolitan Regional I, during the development of the handball project "Educating through sport is social transformation". The choice of this theme is based on my student experience, as I am a student from the sports project of Colégio Estadual Antônio da Silva, a public school in the State of Rio de Janeiro in the municipality of Nova Iguaçu and locus of this research. In addition, I later became a teacher at this school and understood how a sports activity well guided by trained and qualified professionals in the area, helps to improve school performance and reduce school dropout of students who are part of these projects, in addition to contributing to citizenship and training of athletes. I was also a teacher and coordinator of this project since 2001 and I was able to have the opportunity to systematize the tables with information from 2007 to 2018, thus quantifying the number of students who failed and dropped out of school, presented in the research. The Challenges faced by Physical Education teachers are numerous, thus, initiatives such as the one in this publication represent an important step for the advancement of knowledge, contributing in an evident way to the practice of teachers in the area. DOI:https://doi.org/10.56238/sevened2023.006-147